Tensor product and variants of Weyl’s type theorem for p-w-hyponormal operators - Rashid, M. H. M. (Methods of Functional Analysis and Topology, 2021)
A Hilbert space operator T is said to be p-w-hyponormal with 0 < p≤ 1 if |T|^p≥ |T|^p≥ |T^*|^p, where T is the Aluthge transform. In this paper we prove basic properties of these operators. Using these results, we also prove that if P is a Riesz idempotent for a non-zero isolated point λ of the spectrum of T, then P is self-adjoint. Among other things, we prove these operators are finitely ascensive and that, for non-zero p-w-hyponormal T and S, TS is p-w-hyponormal if and only if T and S are p-w-hyponormal. Moreover, it is shown that property (gt) holds for f(T), where fH_nc(σ(T)). Оператор T у гільбертовім просторі називається p-w-гіпонормальним, де 0 < p≤ 1, якщо |T|^p≥ |T|^p≥ |T ^*|^p, де T — перетворення Алутге. В цій роботі досліджені основні властивості таких операторів. Показано також, що якщо P — ідемпотент Рісса, який відповідає ненульовій ізольованій точці λ спектру T, то оператор P самоспряжений. Доведено, що ці оператори мають скінченний підйом і що для ненульових p-w-гіпонормальних T і S, TS є p-w-гіпонормальним тоді й тільки тоді, коли T і S p-w-гіпонормальні. Крім того, доведено, що властивість (gt) має місце для f(T), де fH_nc(σ(T)).